Accident reconstruction : technology and animation. (Society of Automotive Engineers, 1991)
Stiffness parameters for vehicle collision analysis - Rear stiffness coefficients derived from barrier test data - Missing vehicle algorithm (OLDMISS) reformulation - Light truck inertial properties - Linear and rotational momentum for computing impact speeds in two-car collisions (LARM) - A two-dimensional model of a "falling" vehicle - The calculation of motorcycle speeds from sliding distances - Heavy truck deceleration rates as a function of brake adjustment - Determinaton of collision configurations from vehicle deformaton patterns - Photographic documentation and analysis in vehicle accident reconstruction - Computer animation. Admissiblility in the courtroom - An application of computer graphics for vehicle accident reconstruction - Computer accident simulation. Pretty pictures and the real world - Engineering visualization of vehicle accidents: data sources and methods of production - Computer-aided accident reconstruction: its role in court - Determination of vehicle crush from two photographs and the use of 3D displacement vectors in accident reconstruction.